Development and Characterization of a Natural Antioxidant Additive in Powder Based on Polyphenols Extracted from Agro-Industrial Wastes (Walnut Green Husk): Effect of Chickpea Protein Concentration as an Encapsulating Agent During Storage - Gutierrez-Cutino, M; Gutierrez-Cutino, M; Matiacevich, S; Soto-Madrid, D (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Developing a powder-form natural antioxidant additive involves utilizing polyphenols extracted from agro-industrial wastes (walnut green husk). This research explores chickpea proteins (CPP) as an emergent encapsulating agent to enhance the stability and shelf life of the antioxidant additive. This study aims to develop a natural antioxidant powder additive based on polyphenols obtained from walnut green husks encapsulated by chickpea protein (5%, 7.5%, and 10% w/v) to evaluate their effect under storage at relative humidities (33 and 75% RH). The physicochemical and structural properties analysis indicated that better results were obtained by increasing the protein concentration. This demonstrates the protective effect of CPP on the phenolic compounds and that it is potentially non-toxic. The results suggest that the optimal conditions for storing the antioxidant powder, focusing on antioxidant activity and powder color, involve low relative humidities (33%) and high protein concentration (10%). This research will contribute to demonstrating chickpea protein as an emerging encapsulating agent and the importance of the cytotoxic analysis of extracts obtained from agroindustrial wastes. © 2024 by the authors.